Characterization methods of zerovalent iron for water treatment and remediation. (1st January 2019) - Li, Jinxiang; Dou, Xiaomin; Qin, Hejie; Sun, Yuankui; Yin, Daqiang; Guan, Xiaohong
Abstract: Appropriately selecting methods for characterizing the reaction system of zerovalent iron (ZVI) favors its application for water treatment and remediation. Hence, a survey of the available ZVI characterization techniques used in laboratory and field studies are presented in this review for clarifying the characteristic properties, ( in-situ ) corrosion processes, and corrosion products of ZVI system. The methods are generally classified into four broad categories: morphology characterization techniques, (sub-)surface and bulk analysis mainly via the spectral protocols, along with the (physio)electrochemical alternatives. Moreover, this paper provides a critical review on the scopes and applications of ZVI characterization methodologies from several perspectives including their suitable occasions, availability, (semi-)quantitative/qualitative evaluations, in/ex-situ reaction information, advantages, limitations and challenges, as well as economic and technical remarks. In particular, the characteristic spectroscopic peak locations of typical iron (oxyhydr)oxides are also systematically summarized. In view of the complexity and variety of ZVI system, this review further addresses that different characterization methods should be employed together for better assessing the performance and mechanisms of ZVI-involved systems and thereby facilitating the deployment of ZVI-based installations in real practice. Graphical abstract: Highlights: The commonly-used methods for characterizing ZVI-based systems are reviewed. The characterization methods of ZVI used in laboratory and field are categorized. The information provided by the characterization methods are presented. The environmental controls of the characterization approaches are discussed. Characterization tools should be used together to clarify reaction mechanisms.